Evaluating the impact of donor eGFR and HLA-DR mismatch on graft survival in living donor kidney transplants - Budhiraja, Pooja; Schold, Jesse D.; Lopez, Rocio; Arrigain, Susana; Kaplan, Bruce (Frontiers in Nephrology, 2025)
BackgroundThis study assesses the impact of human leukocyte antigen (HLA)-DR mismatch and donor-estimated glomerular filtration rate (eGFR) on outcomes of living donor kidney transplantation (LDKT), which are especially relevant to the availability of multiple donors and paired kidney exchanges.MethodsUsing data from the Scientific Registry of Transplant Recipients (SRTR), we retrospectively analyzed graft survival in adult LDKT recipients transplanted between January 2013 and September 2022. Recipients with 0 HLA-DR mismatches were compared to those with 1-2 HLA-DR mismatches. Cox models assessed the association between donor eGFR and graft and patient survival, stratifying by a) HLA-DR mismatches, and b) HLA-DR mismatches and recipient age.ResultsAmong 44,080 recipients, 7,195 had 0 HLA-DR mismatches and 36,885 had 1-2 HLA-DR mismatches. The recipients’ mean age was 49.1 for the 0 HLA-DR mismatch group and 50.4 for the 1-2 HLA-DR mismatch group. The donors’ mean age was 43.1 and 43.8, with an eGFR of 101.0 and 99.9 ml/min, respectively. A higher donor eGFR was associated with better graft survival. Stratified analyses showed higher donor eGFR levels reduced the risk of graft loss in cases with DR mismatch (p < 0.001) but not in cases without HLA-DR mismatch (p = 0.81). This effect was significant for recipients aged 18-39 and over 60. Similar results were observed for patient survival.ConclusionsHigher donor eGFR was associated with lower risks of graft loss and patient death in the HLA-DR mismatch group but not the 0 HLA-DR mismatch group. These results emphasize the importance of considering both HLA-DR matching and donor kidney function, particularly for younger recipients to avoid sensitization for future transplants.